Experimental investigation of optimal particulate sensor location in an aircraft cabin - Shehadi, Maher F. (Kansas State University, 2010)
Each year millions of people travel by commercial aircrafts. The Bureau of Transportation Statistics indicates that about 600 million passengers fly each year in the United States and, of those, roughly 350,000 are international travelers. This number of travelers leaves commercial airliners potentially vulnerable to biological contamination and makes the transmission of diseases a serious threat. The spread of SARS (Severe Acute Respiratory Syndrome) and H1N1 (swine flu) are examples of documented cases. Consequently, considerable research has been and continues to be conducted to study and understand particulate transport mechanisms and dispersion behavior inside aircraft cabins to develop means for detecting, controlling, and removing contaminants from aircraft cabins and to find methods for preventing the aircraft from being used for intentional contaminant deployment. In order to develop means to monitor and control air quality, infectious disease transmission, and particulate transport inside aircraft cabins, an experimental study was conducted to determine the best sensor placement locations for detection and to identify the number of sensors needed to accurately track air quality incidents within a cabin. An 11-row mockup, intended to be representative of a typical wide-body aircraft, was used for the research. The mockup interior is based on the actual dimensions of the Boeing 767 aircraft cabin. Inside the mockup cabin, actual aircraft equipment including seats and air diffusers were used. Each row has seven passenger seats. Particulates were released from different locations in the second row of the mockup cabin. The transported particles were then collected at six different locations in the lateral direction. The best location to place a sensor was defined as the location having the strongest signal (maximum number of particles collected) or the fastest detection time. After determining the best location in the lateral direction, particles were collected at the same location, but in different rows to estimate the differences between the signal strength and the delay time in detecting the signal from row to row. For the later investigation, the particulates were released in Row 2 and in Row 6 as well. For the six locations examined, it was found that the best location for the placement of a sensor in the 11-row mockup in the lateral direction is on the centerline near the cabin floor. Longitudinally, it was found that a sensor may be used for detecting particulates in the same row as the release and a row in front and in back of the release location. For the mockup cabin, a total of 4 sensors was recommended to monitor particulate releases in the 11 row mockup cabin, each of these sensors separated by two rows.
Keywords: Air Quality; Aircraft Cabin; Sensor Location; Engineering, Environmental (0775); Engineering, Mechanical (0548)